2021
DOI: 10.3390/cancers13030502
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors for Pancreatic Cancer and Its Early Detection Using Special Pancreatic Ultrasonography in High-Risk Individuals

Abstract: Because pancreatic cancer has a dismal prognosis, a strategy for early diagnosis is required. This study aimed to identify predictive factors of neoplastic progression in patients at high risk for pancreatic cancer and examined the efficiency of surveillance using transabdominal special ultrasonography focusing on the pancreas (special pancreatic US). Patients with slight main pancreatic duct (MPD) dilatation (≥2.5 mm) and/or pancreatic cysts (≥5 mm) were enrolled in a prospective surveillance study with speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 34 publications
0
14
0
1
Order By: Relevance
“…Pancreatic cancer is estimated to be the fourth leading cause of death and generally has a poor prognosis, with a 5-year overall survival (OS) rate of 10% at all stages [ 1 ]. Pancreatic cancer is difficult to diagnose at an early stage [ 2 , 3 ], and more than half of patients with pancreatic cancer are diagnosed at unresectable stages [ 4 , 5 ]. Chemotherapy has contributed to improvements in the prognosis of patients with unresectable pancreatic cancer [ 4 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pancreatic cancer is estimated to be the fourth leading cause of death and generally has a poor prognosis, with a 5-year overall survival (OS) rate of 10% at all stages [ 1 ]. Pancreatic cancer is difficult to diagnose at an early stage [ 2 , 3 ], and more than half of patients with pancreatic cancer are diagnosed at unresectable stages [ 4 , 5 ]. Chemotherapy has contributed to improvements in the prognosis of patients with unresectable pancreatic cancer [ 4 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Da ein generelles Pankreaskarzinomscreening der Allgemeinbevölkerung, wie oben angegeben, nicht durchführbar ist, kommt der Abdominalsonografie in diesen Fällen eine herausragende Bedeutung zu. Aus Kostengründen wäre es in individuellen Fällen durchaus zu erwägen, die intensiven Verlaufsuntersuchungen zystischer Pankreasveränderungen intervallmäßig alternierend auch durch abdominalsonografische Kontrolluntersuchungen zu ergänzen [54,55].…”
Section: Abdominalsonografie Zur Frühdiagnose Von Pankreaskarzinomenunclassified
“…Special pancreatic ultrasonography demonstrated superiority over conventional transabdominal ultrasonography in detecting pancreatic cysts [ 16 ]. Recently, we found that early detection of PC and favorable prognoses were achieved by surveillance, mainly with special pancreatic ultrasonography, in high-risk individuals with pancreatic cysts and/or dilatation of the main pancreatic duct (MPD) (defined as an MPD diameter of ≥2.5 mm) [ 7 ].…”
Section: Introductionmentioning
confidence: 99%